A class of nonlinear double-phase Dirichlet fractional differential equations - Zeng, Shengda; Cen, Jinxia; Vanterler da C. Sousa, José (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, we study the existence of positive solutions for a new class of double-phase Dirichlet fractional differential equations with singular and superlinear terms. By applying the Nehari manifold method we show that for all small values of the parameter τ > 0, the considered equation has at least two positive solutions.
Keywords: psi-Hilfer fractional derivative; double-phase problem; positive solution; singularity